2014
DOI: 10.1039/c3gc41357h
|View full text |Cite
|
Sign up to set email alerts
|

Control of selectivity, activity and durability of simple supported nickel catalysts for hydrolytic hydrogenation of cellulose

Abstract: Efficient conversion of cellulose to sorbitol and mannitol by base metal catalysts is a challenge in green and sustainable chemistry, but typical supported base metal catalysts have not given good yields of hexitols or possessed durability. In this study, it has been demonstrated that a simple carbon-supported Ni catalyst affords up to 67% yield of hexitols in the conversion of cellulose, and that the catalyst is durable in the reuse experiments for 7 times. In addition, the catalyst can be separated by a magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 40 publications
3
43
0
1
Order By: Relevance
“…As shown in Table 2, the conversion was maintained but the yield of 2 decreased to 32-33% in the second and third runs, and the yield of 5 increased (Entries [16][17][18]. This indicates that the hydrogenation or dehydrogenation ability of Ni particles decreases in the reuse experiments.…”
Section: Catalytic Aqueous-phase Hdo Of 4-propylphenolmentioning
confidence: 69%
See 1 more Smart Citation
“…As shown in Table 2, the conversion was maintained but the yield of 2 decreased to 32-33% in the second and third runs, and the yield of 5 increased (Entries [16][17][18]. This indicates that the hydrogenation or dehydrogenation ability of Ni particles decreases in the reuse experiments.…”
Section: Catalytic Aqueous-phase Hdo Of 4-propylphenolmentioning
confidence: 69%
“…The leaching amount of Ni was only 45 ppm, corresponding to 10wt% of catalyst, and that of Re was less than detection limit (2 ppm). Hence, the deactivation may be due to the slight oxidation of the Ni surface [17]. a Reaction conditions: 4-propylphenol 1 5.0 mmol, Re-Ni/ZrO 2 0.2 g, 10 wt% Ni loading, Re/Ni molar ratio 0.33, water 40 mL, initial H 2 pressure at RT 4 MPa, 300 ˚C, 1 h, 600 rpm.…”
Section: Catalytic Aqueous-phase Hdo Of 4-propylphenolmentioning
confidence: 99%
“…We also tested Pt and Ni catalysts that showed good activity in the hydrolytic hydrogenation of cellulose. 27,28 However, Pt/TiO 2 and Ni/TiO 2 were inactive for the formation of ADS (2.9% and 0.3% yields, respectively; entries 5 and 6), regardless of the higher loading amounts of metals. Such a low activity of Pt was previously observed in the hydrolytic hydrogenation of hemicellulose in beet fibre containing proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing metal loadings can increase the particle size and accordingly improve the catalyst stability. Fukuoka et al showed that larger crystalline Ni particles were more resistant to sintering and to oxidation on the surface [56]. Another way to improve the stability of a metallic catalyst is modifying it with a second metal to form a bimetallic catalyst [27,57].…”
Section: Catalysts and Reaction Mechanismsmentioning
confidence: 99%